PENDIDIKAN INKLUSIF SEBAGAI STRATEGI DALAM MEWUJUDKAN PENDIDIKAN UNTUK SEMUA - Abdul Rahim (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2016)
Education is the right of all children without exception. However, the main one of the main problems of education in Indonesia is not all children have access to education. Not only economic issues but also include physical or psychological conditions that are â€œdifferentâ€ with children in general, or better known as disbilitas. They (disbalitas) are vulnerable to marginalization especially in the field of education. In the last 10 years the Indonesian government has launched inclusive education and the main purpose is to accommodate the rights of every child to be able to not only disability. Hope that further is to realize the ideals of the 1945 Constitution that â€œthe intellectual life of the nationâ€.